Facile Separation, Spectroscopic Identification, and Electrochemical Properties of Higher Trifluoromethylated Derivatives of [70]Fullerene. Issue 15 (16th July 2018) - Kosaya, Maria P.; Rybalchenko, Alexey V.; Lukonina, Natalia S.; Mazaleva, Olga N.; Ioffe, Ilya N.; Markov, Vitaliy Yu.; Troyanov, Sergey I.; Sidorov, Lev N.; Tamm, Nadezhda B.; Goryunkov, Alexey A.
Abstract: We survey the structure and electronic properties of the family of higher trifluoromethylated C70 (CF3 ) n molecules with n= 14, 16, 18, and 20. Twenty‐two available compounds, of which thirteen are newly obtained and characterized, demonstrate the broad diversity of π‐system topologies, which enabled us to study the interplay between the CF3 addition pattern and the electronic properties. UV/Vis spectroscopic and cyclic voltammetric studies demonstrate the importance of the exact addition pattern rather than the plain number of addends. Of particular interest is the skew pentagonal pyramid (SPP) addition pattern, which enables formation of closed‐shell cyclopentadienyl anions C70 (CF3 ) n −1 − through CF3 detachment upon electron transfer. A detailed study of the process is presented for a SPP‐C70 (CF3 )16 where potentiostatic electrolysis at the second reduction potential gives C70 (CF3 )15 − oxidizable to a persistent C70 (CF3 )15 · radical. Together with the literature data for the lower C70 (CF3 ) n compounds with n= 2–12, the present results show good correlation between the experimental boundary level positions and the DFT predictions. The compounds turn out to be electron acceptor molecular semiconductors with experimental LUMO energies and HOMO–LUMO gaps within the ranges of −4.3 to −3.7 eV and 1.6 to 3.3 eV, respectively, depending on the shape of the conjugated fragments. The HOMO levels fall within the range of −5.6 to −6.9 eV and show linear correlation with the number of addends. Abstract : Trifluoromethylated [70]fullerenes : The first comprehensive spectroscopic, electrochemical, and computational characterization of the higher trifluoromethylated C70 (CF3 ) n compounds with n= 14, 16, 18, and 20 reveal remarkable variations of the LUMO energy and the HOMO–LUMO gap.